2017
DOI: 10.1111/1475-4932.12382
|View full text |Cite
|
Sign up to set email alerts
|

Baby Bonuses: Natural Experiments in Cash Transfers, Birth Timing and Child Outcomes

Abstract: We use the 1 July 2004 introduction of the Australian Baby Bonus to identify the effect of family income on child test scores at grade three. Using a difference‐in‐differences design, we find no evidence that the Baby Bonus improved child outcomes in aggregate, but some evidence of a modest effect for children from disadvantaged backgrounds. We examine whether birth shifting associated with the Baby Bonus and two other Australian maternity payments had negative long‐term effects on children. Despite widespread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 21 publications
2
34
0
Order By: Relevance
“…However, it is not surprising that an unconditional program leads to a null eect on the well-being of families. This is conrmed by evidence on universal family benets that found no impact on child and parent well-being (Hener, 2016 ;Gaitz and Schurer, 2017 ;Deutscher and Breunig, 2018 ;González, 2018).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…However, it is not surprising that an unconditional program leads to a null eect on the well-being of families. This is conrmed by evidence on universal family benets that found no impact on child and parent well-being (Hener, 2016 ;Gaitz and Schurer, 2017 ;Deutscher and Breunig, 2018 ;González, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…25. Gaitz et al (2017) and Deutscher et al (2018) found no evidence that unconditional cash transfers in Australia are eective in boosting learning and cognitive scores.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…were born prior to the introduction of the baby bonus scheme). It appears this did have some effect for children from disadvantaged backgrounds (Deutscher & Breunig, ).…”
Section: Program Evaluation and Natural Experimentsmentioning
confidence: 99%